Why Biden-era clean energy investment policies had limited political returns - Alexander F. Gazmararian; Nathan M. Jensen; Dustin Tingley (Proceedings of the National Academy of Sciences, 2026)
The Biden Administration enacted the largest federal policy framework to incentivize clean energy and decarbonization in U.S. history. We examine whether Biden-era green investments produced political returns by affecting public opinion. Using geolocated survey data linked to investment records and a database of company and politician statements, we assess project visibility and credit attribution. People closer to new renewable energy and green manufacturing facilities are more likely to notice these investments but are not more likely to credit the Biden Administration. Instead, the public sees governors as most responsible. This credit allocation pattern aligns with the political message environment: Governors more frequently claim credit than the White House and companies spread recognition broadly across political actors. This fragmented information environment illustrates the limits of using less traceable forms of green spending to generate electoral gains and public support for climate policy.